Simple Clinical Photokeratoscopy - Sivak, Jacob G; Strong, Graham (Canadian Journal of Optometry, 1982)
A simple photokeratoscope can be clinically useful for the quantification of corneal configuration in keratoconus, for determining the presence or absence of large corneal cylinders in infants and non-communicative patients and for recording post-operative corneal topography.